Pengaruh Keselamatan dan Kesehatan terhadap Kinerja Karyawan PT. Daya Patra - Arum, Sulistyorini; Ma'rifatul M, Amalia (Jurnal Teknologi dan Manajemen Sistem Industri, 2022)
Performance is the most important aspect in achieving goals with maximum results from the performance of a good team or individual company. And vice versa, failure to achieve the formulated goals is the result of inefficient team or individual performance. the influence of employee safety and health on employee performance greatly determines the company's progress, this is due to the maximum worker conditions that will affect the results of their performance. This research uses multiple linear regression method because it uses x and y variables. In the regression method we have to distribute questionnaires to the respondents we are aiming for. This calculation uses the Multiple Linear Regression method with employee performance as the dependent variable (Y) and employee health and safety as the influencing variable (X). From the results of multiple linear regression analysis, it was found that the variable Health (X1) did not affect employee performance (Y) and safety (X2) had a linear effect on employee performance (Y). With a linear result Y = 1.652 –0.120 x1 + 1.046 x2.